2000
DOI: 10.1111/0022-1082.00206
|View full text |Cite
|
Sign up to set email alerts
|

Bad News Travels Slowly: Size, Analyst Coverage, and the Profitability of Momentum Strategies

Abstract: Various theories have been proposed to explain momentum in stock returns. We test the gradual-information-diffusion model of Hong and Stein (1999) and establish three key results. First, once one moves past the very smallest stocks, the profitability of momentum strategies declines sharply with firm size. Second, holding size fixed, momentum strategies work better among stocks with low analyst coverage. Finally, the effect of analyst coverage is greater for stocks that are past losers than for past winners. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

155
1,115
18
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,237 publications
(1,338 citation statements)
references
References 45 publications
155
1,115
18
12
Order By: Relevance
“…For example, Demir et al (2004), Rouwenhorst (1998), Hong et al (2000), Hameed and Kusnadi (2002), Siganos (2007) etc., have documented the positive effect of small-size stocks on profitability of the momentum strategy. On the contrary, other studies have failed to document any evidence to separate contribution of small-size stocks on profitability of the momentum strategy such as the studies by T. Hou and Mcknight (2004), Mengolie (2004) etc.…”
Section: Sizementioning
confidence: 99%
“…For example, Demir et al (2004), Rouwenhorst (1998), Hong et al (2000), Hameed and Kusnadi (2002), Siganos (2007) etc., have documented the positive effect of small-size stocks on profitability of the momentum strategy. On the contrary, other studies have failed to document any evidence to separate contribution of small-size stocks on profitability of the momentum strategy such as the studies by T. Hou and Mcknight (2004), Mengolie (2004) etc.…”
Section: Sizementioning
confidence: 99%
“…The momentum factor is the difference in returns between a portfolio of winners and a portfolio of losers. Hong, Lim and Stein (2000), Jegadeesh (1990), Jegadeesh andTitman (1993, 2001), and Nijman et al (2004) examined momentum returns of firm size and value. The findings show that momentum effect is more in small cap stocks in the respective markets studied.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the momentum factor was statistically significant along with the size and value factors. Subsequently, Hong et al (2000), investigated return momentum effect on the basis of size. Nonetheless, they found that portfolio of stocks with the highest market value has non-existent of momentum effect.…”
Section: Introductionmentioning
confidence: 99%
“…Lesmond et al (2001) montrent que les coûts de transaction sont corrélés négativement à la taille des entreprises et au prix des titres et que la rentabilité des stratégies de momentum est reliée positivement aux coûts de transaction. Hong et al (2000) concluent que la rentabilité des stratégies de momentum décroît avec la taille des entreprises et le suivi des analystes financiers, et ce plus spécifiquement pour les portefeuilles perdants. Daniel et Titman (1999) identifient que la rentabilité des stratégies de momentum est plus élevée pour les titres de croissance que pour les titres de valeur.…”
Section: Autres Explications Non Reliées Au Risqueunclassified